Nanocellulose composite gel with high ionic conductivity and long service life for flexible zinc-air battery - Ziyuan Li (Elsevier, 2021)
Zinc-air batteries with high theoretical energy density have gained tremendous research interest as one of the candidate energy storage devices for flexible and portable electronic devices. Improving the performance of solid-state batteries (such as work stability, service life, etc.) has become a significant problem at present, and the choice of the ideal flexible solid electrolyte material as a “bridge” plays a vital role in flexible batteries. In this work, a polyvinyl alcohol (PVA)-based cellulose composite hydrogel electrolyte (HGE) was synthesized by carboxyl modified nanocellulose (C-CNFs), and the optimum adding amount of C-CNFs was screened. The PVA-based cellulose composite HGE had excellent environmental stability and high ion migration efficiency. After standing and full exposure for 48 h at room temperature, the mass loss was only 21.4%, and the initial ion conductivity reaches 3.12 × 10−1S·cm−1. In addition, the composite HGE had a specific improvement in thermal stability and tensile mechanical properties. The assembled flexible zinc-air battery (F-ZAB) showed excellent cycle life and discharge capacity. What's more, the F-ZAB can work continuously and stably at a bending angle of 180° with high flexibility and safety.